2008
DOI: 10.1051/parasite/2008153484
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based methods to the diagnosis of imported malaria

Abstract: Summary :Rapid and precise diagnosis of malaria is needed to take care febrile patient returning from endemic areas. Since the first description of the diagnosis of Plasmodium infection by polymerase-chain-reaction (PCR), the role of this kind of molecular method in the laboratory diagnosis of imported malaria is still a topical question. PCR-based assays were found to be more sensitive and more specific than all conventional methods. The highest contribution of the molecular diagnosis is that a PCR negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 42 publications
3
73
0
Order By: Relevance
“…Polymerase chain reaction (PCR) offers a good alternative to microscopy in terms of sensitivity and specificity and could be used as a confirmatory tool for microscopy identification of malaria parasites (11,12). Molecular methods, such as single-step PCR (13), loopmediated isothermal amplification (LAMP) assay (14), nested PCR (15,16), multiplex PCR (17,18), multiplex real-time PCR (19), and real time PCR (20)(21)(22)(23) basically use conventional PCR techniques to detect and identify malaria parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) offers a good alternative to microscopy in terms of sensitivity and specificity and could be used as a confirmatory tool for microscopy identification of malaria parasites (11,12). Molecular methods, such as single-step PCR (13), loopmediated isothermal amplification (LAMP) assay (14), nested PCR (15,16), multiplex PCR (17,18), multiplex real-time PCR (19), and real time PCR (20)(21)(22)(23) basically use conventional PCR techniques to detect and identify malaria parasites.…”
Section: Introductionmentioning
confidence: 99%
“…PCR is a more sensitive and specific method of diagnosis than microscopy. 22,23 The low prevalence of congenital malaria observed in this study could also be because of the design (cross-sectional); hence, single sets of blood samples were only collected within the first 24 hours of birth. Other studies that followed-up babies for longer periods of time after birth reported higher prevalence of congenital malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Although the qPCR method requires specific material and is more expensive than mi-Prevalence of P. falciparum and P. vivax in Pará State croscopy and conventional PCR (Berry et al, 2005), it presents advantages of rapidity, lower contamination, and better standardization and can be used for routine testing, particularly for the study of populations in endemic areas in which patients may be asymptomatic (Mens et al, 2007;Boonma et al, 2007;Gama et al, 2007;Veron et al, 2009) and in patients who have negative results on routine methods but are strongly suspected of having malaria (Bourgeois et al, 2010). Thus, qPCR assay based on the detection of mitochondrial cytochrome c oxidase genes may be the method of choice for specific situations, including detection in low-parasitized individuals.…”
Section: Discussionmentioning
confidence: 99%